IMPACT OF ENDEMICITY OF ASCARIASIS ON DIAGNOSIS OF ACUTE APPENDICITIS: Endemicity of Ascariasis - Ahmed, Naveed; Gul, Mian Sarfraz; Pervaiz, Hafiz Khalid; Ahmed, Iftikhar; Ali, Mujahid Zulfiqar; Ali, Shafaqat (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the impact of endemicity of ascariasis in the manifestation of acute appendicitis. Study Design: Prospective observational study. Place and Duration of Study: General Surgery Department, Combined Military Hospital Skardu, from May 2012 to Apr 2015. Methodology: Patients presenting with symptoms of acute appendicitis were included in the study. Patients were diagnosed after taking detailed history, clinical examination and blood chemistry. All the patients underwent open appendectomy under general anesthesia. Per-operatively presence of worms was assessed in terminal ileum and after that in the lumen of the appendix initially by palpation and then by opening its lumen after it was removed. Histopathologic diagnosis could not be confirmed due to its non-availability as the surgeries were performed in a remote and resource constraint area of the country. Results: A total of 224 patients were included in the study. Out of these, 143 (63.8%) were male and 81 (36.1%) female patients. The mean age of patients was 22 ± 6 years. Per-operatively, 21 (9.3%) patients had worms in both ileum and appendicular lumen while 22 (9.8%) patients had worms only in the terminal ileum and there were no worms seen in either ileum or appendix in 181 (80.8%) patients. Conclusion: There is a relation of parasitic infestation especially Ascaris lumbricoides in the manifestation of acute appendicitis in endemic areas.